2015
DOI: 10.1038/srep09241
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Action of Domain II and IV Underlies Persistent Current Generation in Nav1.3 as revealed by a tarantula toxin

Abstract: The persistent current (INaP) through voltage-gated sodium channels enhances neuronal excitability by causing prolonged depolarization of membranes. Nav1.3 intrinsically generates a small INaP, although the mechanism underlying its generation remains unclear. In this study, the involvement of the four domains of Nav1.3 in INaP generation was investigated using the tarantula toxin α-hexatoxin-MrVII (RTX-VII). RTX-VII activated Nav1.3 and induced a large INaP. A pre-activated state binding model was proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 61 publications
5
13
0
Order By: Relevance
“…This toxin increases Nav1.3-mediated I NaP via interaction with DII and DIV. 55 Interestingly, focal application of RTX-VII to the surface of the cerebral cortex of adult rats induced seizures, consistent with a potentially ictogenic effect of increased Nav1.3 I NaP and supporting the pathogenic mechanism proposed here. Why the p.Pro1333Leu mutation, located in DIII, also increased I NaP , remains unclear.…”
Section: Discussionsupporting
confidence: 79%
“…This toxin increases Nav1.3-mediated I NaP via interaction with DII and DIV. 55 Interestingly, focal application of RTX-VII to the surface of the cerebral cortex of adult rats induced seizures, consistent with a potentially ictogenic effect of increased Nav1.3 I NaP and supporting the pathogenic mechanism proposed here. Why the p.Pro1333Leu mutation, located in DIII, also increased I NaP , remains unclear.…”
Section: Discussionsupporting
confidence: 79%
“…These results indicated that JZTX-I was not selective for hNav1.5, but instead interacts with several VGSC subtypes. This is in contrast to JZTX-II and JZTX-III (Rong et al, 2011;Tao et al, 2013a), another peptide toxins isolated from the same venom of Chilobrachys jingzhao, which are selective for hNav1.5. Given that JZTX-I and JZTX-II are similar in function but differ in isoform selectivity, a comparison of these two toxins should improve our understanding of the structural characteristics that determine toxin selectivity.…”
Section: Discussionmentioning
confidence: 61%
“…Data were analyzed by softwares igo pro 6.10A, Excel 2010 and sigmaplot 10.0. Whole‐cell patch‐clamp recordings were performed as previously described .…”
Section: Methodsmentioning
confidence: 99%